(untitled) (Sains Humanika, 2011)
The aim of this study was to determine the effects of a Modified Collaborative Strategic Reading (MCSR) intervention on reading performance among first-year students in a public university in Iran. A quasi-experiment method using a pre-test-post-test design was utilized. The intervention was implemented to 42 Iranian university-level EFL freshmen. The students met once a week and received the MCSR intervention for 90 minutes over six weeks. A researcher-developed reading comprehension test was group administered at the pre- and posttests. Upon completion of the study, studentsâ€™ perceptions regarding the MCSR intervention were also evaluated by means of an OpinionnaireÂ®. Quantitative results indicated that participating students did not demonstrate significant gains in reading comprehension skills. However, qualitative evaluation revealed that students did have positive attitudes towards the MCSR intervention. We postulate that the participants may require intervention of considerably greater intensity in terms of instructional dosage than that provided in this research. Additionally, the data show that the students have a strong preference for communicative and cooperative activities and the popular thinking that they might resist group work (because of their long-standing conventional learning tradition) can no longer be true.